Early Ophthalmic Changes in Macula Does Not Correlate with Visual Function - Narayanan D; Wallstrom G; Rodriguez J; Welch D; Chapin M; Arrigg P; Patil R; Abelson M (Clinical Ophthalmology, 2020)
Divya Narayanan,1 Garrick Wallstrom,2 John Rodriguez,1 Donna Welch,1 Matthew Chapin,1 Paul Arrigg,3,4 Rajkumar Patil,1 Mark Abelson1,4,5 1Ora, Inc, Andover, MA, USA; 2Statistics and Data Corporation, Tempe, AZ, USA; 3Joslin Diabetes Center, Boston, MA, USA; 4Ophthalmology, Harvard Medical School, Boston, MA, USA; 5Ophthalmology, Massachusetts Eye and Ear, Boston, MA, USACorrespondence: Divya NarayananOra, Inc., 300 Brickstone Square, Andover, MA 01810, USATel +1 978-685-8900Fax +1 978-689-0020Email dnarayanan@oraclinical.comPurpose: Early detection and treatment of age-related macular degeneration require a clear understanding of the early progress of the disease. The purpose of this study was to investigate whether minimal macular ophthalmoscopic changes corresponded to changes in visual function.Methods: Color macular photos from a group of older subjects who were classified as grade 0 on AREDS simplified grading were further evaluated by a retinal specialist using 5x magnification for possible minimal macular anomalies. Group 0-A (N = 15) were defined as subjects with no visible macular anomalies while Group 0-B (N = 19) comprised subjects for whom minimal macular mottling, pigment changes or very small drusen (< 63 μm) were observed in the study eye. All subjects had best VA of 20/25 or better and had no evidence of other retinal diseases in the study eye. All subjects underwent a series of visual function tests such as standard ETDRS VA, low luminance ETDRS VA, Pelli-Robson contrast sensitivity, variable contrast flicker (VCF) sensitivity, and reading speed (words per minute, wpm) using both MNRead and low luminance reading on a tablet.Results: There was no significant difference between the mean age between the two groups (74.8 ± 5.2 years for 0-A vs 74.5 ± 4.4 for 0-B, p = 0.82). None of the visual function tests identified any significant difference between the two groups. Mean ETDRS VA was 0.0 ± 0.11 for 0-A subjects and 0.08 ± 0.12 for 0-B (p = 0.063). Mean Pelli-Robson log contrast sensitivity was 1.75 ± 0.29 for 0-A and 1.78 ± 0.17 for the 0-B group (p = 0.73). VCF threshold was 0.47 ± 0.25 for 0-A and 0.43 ± 0.22 for 0-B (p = 0.64). Reading speed using MNRead was 214 ± 47.4 wpm for 0-A and 210 ± 64.7 for 0-B (p = 0.85). Low luminance tablet reading speed was 137 ± 71.8 wpm for 0-A and 151 ± 39.4 (0-B) (p = 0.49).Conclusion: A panel of psychophysical tests did not demonstrate significant differences between subjects with and without minimal macular changes.Keywords: macula, visual function, AMD